ChemInform Abstract: Investigation of Alkyne Regioselectivity in the Ni‐Catalyzed Benzannulation of Cyclobutenones. Issue 25 (5th June 2015) - Stalling, Timo; Harker, Wesley R. R.; Auvinet, Anne‐Laure; Cornel, Erik J.; Harrity, Joseph P. A.
Abstract: In general, the title reaction proceeds with low levels of regioselectivity.